Correlation between baseline anion gap and early acute kidney injury in patients with acute pancreatitis in the intensive care unit: A single-center retrospective cohort study - Yaqing Zhang; Haiping Ma; Rui Wang; Li Li; Qingwei Kong; Cuiping Hao; Ying Zhang; Jinfeng Li (PLoS ONE, 2025)
Objective Acute pancreatitis (AP) is an acute inflammatory disease that can lead to multiple system dysfunction, including acute kidney injury (AKI). AKI occurs in 10%-42% of AP patients, and studies have shown that early (48 hours) acute pancreatitis associated acute kidney injury (AP-AKI) can increases the risk of death in acute pancreatitis. Anion gap (AG) is a common index in clinical evaluation of acid-base imbalance and an important index in critically ill patients. The aim of this study was to investigate the relationship between baseline anion gap values and early acute kidney injury in patients with acute pancreatitis in intensive care unit. Methods Our data were derived from inpatients admitted to Beth Israel Deaconess Medical Center (BIDMC) in the United States between 2008 and 2019. A total of 4,017 adult patients with acute pancreatitis admitted to the ICU were enrolled in the study, and 475 were enrolled according to the exclusion and inclusion criteria. Only the baseline value and one day after arrival to the intensive care unit (ICU) were considered for all laboratory test values. According to previous literature and clinical significance, AG was divided into two groups: low value (< 16mmol/L) group and high value (≥16mmol/L) group, and logistics univariate and multifactor regression analysis was applied to verify the relationship between anion gap and AKI risk. Results Only 157 of the 475 AP cases had an AG level below 16 mmol/L, whereas 318 patients had an AG level over 16 mmol/L. Within 48 hours, 89 and 240 cases (56.7% and 75.5%) and the low- and high-AG groups had AKI. In AP cases, an elevated AG was related to an increased risk of AKI [odds ratio (OR) = 1.06, 95% confidence interval (CI): 1.03–1.1], and is a nonlinear relationship. When controlling for other factors, this correlation was still significant. Compared to the lower group, high-AG (≥16mmol/L) values can increase the risk of early acute kidney injury in patients with acute pancreatitis (OR = 2.35, CI: 1.57–3.53). Conclusion Anion gap (AG) is an independent risk factor for early acute kidney injury in patients with acute pancreatitis, and has a nonlinear relationship with 48-hour AKI. Higher AG(≥16mmol/L) values can significantly increase the risk of AP-AKI.